Determinan Keberhasilan Usaha UMKM - Dwi Saraswati; Yunita Sari Rioni; Ikhah Malikhah; Ardhansyah Putra Hrp (Journal of Trends Economics and Accounting Research, 2023)
This study examines whether accounting information variables and leadership variables can affect the success rate of a business. Then the data obtained were analyzed using multiple regression analysis, data normality test, heterochedasticity test, partial test (t-test), simultaneous test (F-test), test and determination test. The results of the study stated that the variables of accounting and leadership information had a significant effect on the business success rate of young MSMEs in Kota Pari Pantai Cermin. The results showed that accounting and leadership information simultaneously had a significant effect on business success with a calculated F value of 1026,250 > a table F value of 3.24. Partial tests also showed that accounting and leadership information respectively had a positive and significant effect on the success of the business, where the value of t count the calculated variable of the accounting information is 2.623 and the t count of the leadership variable is 45.304 where each is greater than the value of t of the table of 2.02. The Adjusted R Square value obtained from the test results of the Coefficient of Determinants (R2) on business success of 0.981 explained that 98.1% of business success can be explained by accounting and leadership information as independent variables. While the remaining 1.9% was explained by other variables that were not studied in this study.